Development of a new process for expanding stepped tapered rings - Markov, Oleg; Gerasimenko, Oleksiy; Aliieva, Leila; Shapoval, Alexander; Kosilov, Maksym (Eastern-European Journal of Enterprise Technologies, 2019)
A new method for expanding large-size tapered rings with a stepped profile has been considered. The proposed method consists in expanding the blank with the help of a stepped die. A procedure for conducting studies by the method of finite elements was proposed. The procedure is intended to determine dependences of the stress-strain state and shape change during the expanding process by means of a stepped die. Variable parameters included relative height of the stepped blank protrusion which varied in the range of 2.2...2.5. Based on the finite-element modeling, distribution of deformation rate in the forging section after expanding with the help of a stepped die was established. The forging taper formed by expanding in this way was determined. Results of finite-element modeling were verified by experimental studies with lead and steel specimens. A procedure for conducting experimental studies was proposed. The finite-element modeling has allowed us to establish that expanding with the help of a stepped die results in a tapered forging shape. This is explained by the fact that when the wall is reduced, tangential deformation of the annular blank in the wall zone is larger than that in the protrusion zone because of different height of the stepped blank. The results of finite-element modeling were confirmed by experiments in laboratory conditions with lead and steel specimens. Increase in diameter of the blank protrusion leads to an increase in rate of the protrusion deformation which causes an increase in diameter of the protrusion bore. Analysis of macrostructure of the annular forging with a tapered stepped profile has made it possible to establish that when the stepped blank is shaped with the help of a stepped die, metal fibers repeat the target part contour which prevents their cutting during machining. The study has established that expanding of stepped tapered blanks is realizable. It expands technological potentials of the process of expanding large-sized forgings